Violence against Women by their Husband and Postpartum Depression - Budhathoki, N; dahal, M; Bhusal, S; Ojha, H; pandey, S; Basnet, S (Journal of Nepal Health Research Council, 2013)
Background: Violence against women in developing countries is very high with very little to choose between the cities and provinces. In Nepal too, violence against women is very rampant. This occurs despite physical violence against women being ascribed as criminal act by Domestic Violence Act. The main objective of the study was to see the association between postpartum depression and violence against women. Methods: A prospective cohort study was conducted among pregnant women of reproductive age group in two centers. Standard questionnaires were used to collect data regarding violence and for detecting postpartum depression. Three interviews one in antenatal and two in postnatal period were taken. Results: The incidence of postpartum depression was found to be 19.4 % (95% CI = 14.73 - 24.06) and 22.22% (95% CI = 17.30 - 27.09) during first (6 week postpartum) and second (10th week) postpartum interview respectively. The incidence of physical, psychological and sexual violence was found to be 20.8% (95%CI= 16.01 - 25.58), 19.4% (95%CI= 14.73 - 24.06) and 13.9% (95% CI= 9.82 - 17.97) respectively. No statistically significant relationship could be found between different forms of violence and postpartum depression .The study showed that all the women with bad communication or conversation with the husband had postpartum depression while only 17.1% of women with good conversation had postpartum depression. Conclusions: No form of violence against women had statistically significant association with development of postpartum depression among Nepalese population. Keywords: cohort study; postpartum depression; violence.